Conceptual DFT, QTAIM, and Molecular Docking Approaches to Characterize the T-Type Calcium Channel Blocker Anandamide - Rangel-Galván, Maricruz; Castro, María Eugenia; Perez-Aguilar, Jose Manuel; Caballero, Norma A.; Melendez, Francisco J. (Frontiers in Chemistry, 2022)
Graphical Abstract